RELATIONSHIP BETWEEN CD34/CD45 POSITIVE CELLS CONCENTRATION IN BLOOD OF HEART RECIPIENTS AND LEVEL OF GRAFT VASCULOPATHY RISK BIOMARKERS - O. P. Shevchenko; R. M. Kurabekova; E. V. Naumova; S. A. Lugovskaya; E. A. Spirina; V. N. Poptsov; G. A. Olefirenko; V. V. Dolgov (Вестник трансплантологии и искусственных органов)
Aim. To determine the relationship between CD34/CD45 positive cells number in peripheral blood before and after heart transplantation (HTx) and plasma level of the biomarkers. Materials and methods. We studied 27 pts. (23 men; 40 ± 13 years) with heart failure caused by dilated (17 cases) or ischemic cardiomyopathy (10 cases) before and after HTx. CD34/CD45 positive cells were measured in peripheral blood before and 2–4 days after the operation by flow cytometry and expressed in number of the cells per 106 events, plasma level of the biomar- kers – by ELISA. Results. The number of CD34/CD45+ cells in pts. with heart failure (224 ± 166) was similar to those in healthy individuals (233 ± 120) and there was no significant difference in the cell number between pts. with dilated (253 ± 188) and ischemic cardiomyopathy (169 ± 100). The cell number did not correlate with age, sex, body weight, blood cells counts and preoperative levels of the biomarkers: PlGF, sCD40L, PAPP-A. In 2–5 days after HTx the cell number decreased to 103 ± 102. The cell number after HTx did not correlate with demographic and laboratory parameters, anesthesia, operation, ischemia and hypothermia duration, blood loss volume and preoperative levels of PlGF and PAPP-A but correlated with sCD40L level in pts. with ischemic cardiomyopathy. Conclusion: Circulating HSC number in patients with heart failure does not differ from those in healthy individuals and decreases after HTx. In patients with ischemic cardiomyopathy the cell number after transplantation associates with preoperative level of sCD40L – the negative predictor of vasculopathy.